Germinative pretreatments to dormancy break in Guazuma ulmifolia Lam. seeds - De Araújo, João Correia [UNESP]; De Aguiar, Neto Ivor Bergemann [UNESP] (My University, 2000)
Guazuma ulmifolia is a typical tree species of secondary forests in Brazil, recommended for restoring degraded areas. Their seeds own a mechanical layer in the tegument and slow, irregular and low germination. This work aimed to evaluate methods to dormancy break in order to increase and accelerate seed germination in this species. The fruits were harvested in Jaboticabal, São Paulo, Brazil, in October 1995 and October 1996, and stored in dry chamber. Four experiments were conducted and the seeds were extracted in the date of installation of each experiment. In the first experiment, the seeds were immersed in concentrated sulphuric acid for 0, 10, 15, 20 and 25 min. Germination tests were conducted at 30 °C and it was included one treatment in which the unscarified seeds were incubated at 20-30 °C. In the second experiment, the immersion period was increased until 100 min, in intervals of 10 min, and the seeds of all the treatments were incubated both at 30 °C and 20-30 °C. Ungerminated seeds were submitted to tetrazolium test in order to verify their viability. In the third experiment, both scarified (immersion in sulphuric acid for 50 min) and unscarified seeds were imbibed in 0, 50, 100 and 150 ppm gibberellic acid (GA3) and incubated at 30 °C. In the fourth experiment, freshly and one year stored seeds were used, scarified (immersion in sulphuric acid for 50 min) and unscarified, and incubated at 30 °C. In all the experiments, both germination percentage and speed were evaluated, as well as the viable seeds percentage in the second experiment. The results showed that to obtain better germination, seeds should be treated with concentrated sulphuric acid for 40 to 50 min and the germination tests must be conducted at constant temperature, during 28 days. The addition of gibberellic acid and the alternating temperature were not effective to stimulate seed germination. After one year dry storage, seeds retained both water impermeability and initial germinability.
Keywords: Dormancy; Germination; Guazuma ulmifolia; Secondary species; Seed; Viability; Forestry; Fruits; Harvesting; Mechanical permeability; Sulfuric acid; Thermal effects; Incubation; Seeds; Sulfuric Acid; Trees